Can emergency physicians accurately and reliably assess acute vertigo in the emergency department?. (10th March 2015) - Vanni, Simone; Nazerian, Peiman; Casati, Carlotta; Moroni, Federico; Risso, Michele; Ottaviani, Maddalena; Pecci, Rudi; Pepe, Giuseppe; Vannucchi, Paolo; Grifoni, Stefano
Abstract: Objective: To validate a clinical diagnostic tool, used by emergency physicians (EPs), to diagnose the central cause of patients presenting with vertigo, and to determine interrater reliability of this tool. Methods: A convenience sample of adult patients presenting to a single academic ED with isolated vertigo (i.e. vertigo without other neurological deficits) was prospectively evaluated with STANDING (S ponTA neousN ystagmus, D irection, headI mpulse test, standiNG ) by five trained EPs. The first step focused on the presence of spontaneous nystagmus, the second on the direction of nystagmus, the third on head impulse test and the fourth on gait. The local standard practice, senior audiologist evaluation corroborated by neuroimaging when deemed appropriate, was considered the reference standard. Sensitivity and specificity of STANDING were calculated. On the first 30 patients, inter‐observer agreement among EPs was also assessed. Results: Five EPs with limited experience in nystagmus assessment volunteered to participate in the present study enrolling 98 patients. Their average evaluation time was 9.9 ± 2.8 min (range 6–17). Central acute vertigo was suspected in 16 (16.3%) patients. There were 13 true positives, three false positives, 81 true negatives and one false negative, with a high sensitivity (92.9%, 95% CI 70–100%) and specificity (96.4%, 95% CI 93–38%) for central acute vertigo according to senior audiologist evaluation. The Cohen's kappas of the first, second, third and fourth steps of the STANDING were 0.86, 0.93, 0.73 and 0.78, respectively. The whole test showed a good inter‐observer agreement (k = 0.76, 95% CI 0.45–1). Conclusions: In the hands of EPs, STANDING showed a good inter‐observer agreement and accuracy validated against the local standard of care.